Experience of pediatric to adult transition in immunology services: patient experience questionnaire and micro-costing analysis - King, Catherine; Ridge, Katie; Smyth, James; Flinn, Aisling M.; Leahy, Timothy Ronan; Conlon, Niall (Frontiers in Immunology, 2024)
The effective transition from pediatric to adult care for individuals with chronic medical conditions should address the medical, psychosocial and educational needs of the cohort. The views and experiences of service users and their families are an integral component of service development. This study sought to evaluate the current provision of transition services from pediatric immunology services to adult immunology services for patients with a diagnosis of an inborn error of immunity at St. James’s Hospital, Dublin. We gathered patient perspectives on the experience of the transition process using a structured survey. In addition, we adopted a micro-costing technique to estimate the cost of implementing the current standard of care for these patients. Results of a micro-costing analysis suggest that the most significant component of cost in assessing these patients is on laboratory investigation, an area where there is likely significant duplication between pediatric and adult care. Perspectives from patients suggested that the transition period went well for the majority of the cohort and that they felt ready to move to adult services, but the transition was not without complications in areas such as self-advocacy and medication management. The transition process may benefit from enhanced communication and collaboration between pediatric and adult services.